SCREENING OF TOXIC MARINE NITZSCHIA SPECIES (BACILLARIOPHYCEAE) IN MALAYSIA - Suriyanti Su Nyun Pau; Dzulhelmi Muhammad Nasir; Gires Usup (Department of Marine Sciences, Trunojoyo University of Madura, Indonesia, 2017)
Amnesic Shellfish Poisoning (ASP) is a type of intoxication caused by the neurotoxin domoic acid (DA). The diatom genus Nitzschia is capable of producing this toxin. Screening for the presence of toxic Nitzschia spp. was carried out at various estuaries in Malaysia. Nitzschia-like cells were isolated and established into clonal cultures. Late stationary phase of cultures were harvested and tested for toxin production using HPLC. Toxin production and compound was verified by LC-MS. From the analyses, at least three cultures were detected with DA, while the rest of the cultures did not show detectable amounts of DA. The localities of the toxic species are Johor and Sabah. Here we conclude that toxic Nitzschia species are present in Malaysian water.Keywords: diatom, estuary, intoxication, safety, toxic